(untitled) (Global Scientific Review, 2025)
The article explores the scientific and popular approaches of Tatyana Vladimirovna Chernigovskaya to language development and the formation of functional literacy. Special attention is given to the interdisciplinary nature of her research, which combines neurolinguistics, cognitive science, and psycholinguistics. The paper analyzes Chernigovskaya’s views on the role of language in thinking, the importance of reading and critical thinking in shaping an individual’s intellectual potential. Her recommendations for developing functional literacy in the context of digitalization and information overload are also discussed. The significance of an individual approach to education and the need to develop stable cognitive skills from an early age are emphasized.